Splat the Cat and the late library book - Meister, Cari; Scotton, Rob; Eberz, Robert (New York, NY : Harper Festival, an imprint of HarperCollins Publishers, 2016)
Splat becomes a fugitive from the library when he realizes he has an overdue library book.
"Based on the creation of Rob Scotton"--Cover.
Ages 4-8.
Keywords: Splat the Cat (Fictitious character) -- Juvenile fiction; Library overdues -- Juvenile fiction